Image Analysis of Root System Architecture of Tomato Under Salinity - Nur Hanis, Haldi (Universiti Malaysia Sarawak (UNIMAS), 2022)
Plants have evolved a variety of strategies to deal with salt stress. The study focus has lately extended to also include root system architecture (RSA) plasticity in order to expose new salt tolerance features with potential breeding applications. In this study, root growth parameter of 20 tomato genotypes grown in paper-based system were quantified. The root variables examined were the main root length (MRL), number of lateral roots (NLR) and total root size (TRS). The root characteristics were measured using ImageJ and SmartRoot image analysis software. Image-analysis showed that the general root architecture was significantly altered in response to salt, particularly in terms of main root development and range of the lateral roots. VIR 2257, VIR 341, and VIR 884 was discovered to be the most resilient to salt among the tomato cultivars tested in both control and salt treated condition.